2005
DOI: 10.1186/1471-2458-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Injury morbidity in an urban and a rural area in Tanzania: an epidemiological survey

Abstract: Background: Injuries are becoming a major health problem in developing countries. Few population based studies have been carried out in African countries. We examined the pattern of nonfatal injuries and associated risk factors in an urban and rural setting of Tanzania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
110
7
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 22 publications
37
110
7
4
Order By: Relevance
“…The preponderance of males among those injured is consistent with data from the World Health Organization (WHO) and the studies conducted by Ghaffar et al [12], Mock et al [13], and Moshiro et al [14]. Similar to other findings, more males than females suffered from all types of injuries; our study identified 10,262 (67.9%) injured males and 4851 (32.1%) injured females.…”
Section: Discussionsupporting
confidence: 82%
“…The preponderance of males among those injured is consistent with data from the World Health Organization (WHO) and the studies conducted by Ghaffar et al [12], Mock et al [13], and Moshiro et al [14]. Similar to other findings, more males than females suffered from all types of injuries; our study identified 10,262 (67.9%) injured males and 4851 (32.1%) injured females.…”
Section: Discussionsupporting
confidence: 82%
“…Wui et al also reported high Male to Female ratio of 2.25:1 in a trauma epidemiology study conducted in Singapore [2] and preponderance of males among injured was also reported by several other studies [11][12][13][14][15]. [1].…”
Section: Discussionmentioning
confidence: 83%
“…These findings suggest that the magnitude of RTI is high, and is higher than that reported from other developing countries. (14)(15)(16)(17)(18)(19) We examined some possible reasons for this. The majority of the previously published population-based studies on RTI incidence from other countries have reported data that had resulted in loss of activities using 12-months recall period, and most of these had reported proxy data.…”
Section: Discussionmentioning
confidence: 99%